A vector memory system based on wafer-scale integrated memory arrays - Chiueh, T.-C. (Computer Design: VLSI in Computers and Processors (ICCD '93, 1993)
The paper proposes a memory architecture called Wafer-scale Interconnected Memory Array (WIMA), which is intended to replace ultra-high-density monolithic DRAM ICs. This architecture employs the high-performance interconnects provided by multichip module technology, the cache-embedding concept, and prime degree interleaving to expose the DRAM's internal parallelism not exploitable by monolithic DRAMs. Using WIMA modules as the basic building blocks, a high-bandwidth, low latency, and low cost vector memory system is developed that supports parallelism among multiple vector access streams. To mask the long start-up latencies, vector memory accesses are architectured to be split-phased. To alleviate the performance impact of bank conflicts, prime degree memory interleaving is adopted. The major contribution of this work is the development of a novel indexing mechanism for prime degree interleaving, which takes at most two integer divisions for each logical vector memory access.< >